Sustainable development education in relation to the social imaginary in upper secondary education - Vargas y Castillo, María Leticia (2023)
Talking about education today implies a commitment not only to the curricular design of the subjects that constitute academic training, it is a permanent commitment to the environment derived from the situation facing the planet due to the irrational use of natural resources, therefore, it is the responsibility of the educational system to form an education based on the promotion of adequate and sustainable development, creating in students an awareness that favors the preservation of nature, with the intention of contributing to the strengthening of environmental education. This study aims to explain the social imaginary presented by young people in the fifth semester on the sustainable development of the economic-administrative area of the high school college of the State of Oaxaca campus 07 Tuxtepec, methodologically, a motorcycle design was implemented, due to the fact that methods of collection of quantitative and qualitative data analysis (Hernández et al., 2010), the results that were found show, in this particular case, an institutionalized social imaginary in the concepts of responsibility, respect for the environment, environmental awareness and sustainability that represent the ideals to continue with a full life. Quantitatively, it was shown that there is a considerable correlation between the imaginary and education of sustainable development, concluding that an ecocentrism social imaginary of the environment visualizes and represents actions with economic or self-interest, taking into consideration otherness, society, and harm. that it causes to the environment.